Preventing erosion of X-chromosome inactivation in human embryonic stem cells - Marissa Cloutier; Surinder Kumar; Emily Buttigieg; Laura Keller; Brandon Lee; Aaron Williams; Sandra Mojica-Perez; Indri Erliandri; Andre Monteiro Da Rocha; Kenneth Cadigan; Gary D. Smith; Sundeep Kalantry (Nature Communications, 2022)
Cloutier et al. discover that human embryonic stem cells (hESCs) cultured with media containing inhibitors of GSK3 proteins undergo erosion of X-chromosome inactivation, which equalizes X-linked gene expression between females and males. The findings inform the faithful culture of hESCs.